2009
DOI: 10.1097/mat.0b013e31818f0056
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Circulatory Support After Congenital Cardiac Surgery

Abstract: Extracorporeal membrane oxygenation (ECMO) is widely used for circulatory support in pediatric cardiac patients with low cardiac output and hypoxemia after cardiac surgery. We evaluated retrospectively, the efficacy of postoperative ECMO support following congenital cardiac surgery in our hospital. From April 2002 to February 2008, seven patients (median age 30 months) received postoperative mechanical support. Three had complete repair including Fontan circulation and four had palliative repair. In four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In our study, both arterial pH values and lactate levels at ECLS initiation were found statistically significantly lower in those who successfully weaned from ECLS. ECLS is rarely required after congenital heart surgery, with the need varying from 1 to 3.5% of all congenital cardiac surgery cases . In our study, ECLS use after the surgery was 2%.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, both arterial pH values and lactate levels at ECLS initiation were found statistically significantly lower in those who successfully weaned from ECLS. ECLS is rarely required after congenital heart surgery, with the need varying from 1 to 3.5% of all congenital cardiac surgery cases . In our study, ECLS use after the surgery was 2%.…”
Section: Discussionmentioning
confidence: 54%
“…Patients on ECMO require systemic anticoagulation to prevent the coagulopathic process initiated when blood contacts an artificial surface, but this therapy predisposes patients on ECMO to life-threatening hemorrhage (13). The frequency of children with complex congenital heart disease or cardiomyopathies requiring ECMO has increased steadily over the past decade (4, 5), and those placed on ECMO after cardiac surgery already have disturbed coagulation pathways and additional surgical sites, factors that have been hypothesized to confer a greater propensity toward bleeding than other ECMO populations (6). Severe bleeding can make ongoing support impossible and may contribute directly to perioperative mortality (7).…”
mentioning
confidence: 99%
“…All patients who underwent additional operative procedure except case no. 10 were previously reported with details about the clinical course (9). Case no.…”
Section: Resultsmentioning
confidence: 99%